Perbedaan pencapaian hasil belajar siswa dalam pembelajaran fisika antara penerapan model problem based learning dan discovery learning - Windy Andaresta; Amali Putra (Universitas Negeri Padang, 2019)
The aim of this research is to examine comprism of student learning outcomes between problem based learning and discovery learning model in static and dinamic fluid. The population of this research are science students in SMAN 1 Bukittinggi. There are two sample classes in this research, they are experiment class I which applies problem based learning model and eperiment II which applies discovery learning model. The result of this research that there are significant differences in physics learning putcomes between problem based learning and discovery learning model. Based the result of research, author provided some suggestion, that: 1) problem based learning and discovery learning model can both develop physics learning outcomes, but problem based learning is better, 2) in order to increase physics learning outcomes than the findings, it needs to do the next research that combine problem based learning with another teratment.